Glucagon-Stimulated Phosphorylation of Mitochondrial and Lysosomal Membranes of Rat Liver In Vivo - Zahlten, Rainer N. (1972)
The pancreatic hormone, glucagon, stimulates the net uptake of inorganic (32)P in vivo into rat liver and its incorporation into proteins of microsomes, mitochondrial membranes, and lysosomes. Incorporation into cytosolic proteins was enhanced only slightly by glucagon. More than 95% of the protein-bound phosphate is present as phosphoserine. Both the radioactivity and the total amount of protein-bound phosphate are increased after injection of glucagon. Glucagon treatment enhanced (32)P incorporation into the alcohol-ether soluble lipids of mitochondria but did not alter the relative distribution of (32)P in various phospholipid species.